An investigation of professional top-level youth football coaches` questioning practice - Cope, E.; Partington, M.; Cushion, C. C.; Harvey, S. (Qualitative Research in Sport, Exercise and Health, 2016)
To position learners as more central components in the coaching process, scholars suggested that coaches should employ a questioning approach, which may lead to the development of desirable learner outcomes (i.e. increased problem solving and decision-making skills). Studies, however, indicate that coaches rarely employ questions within their practice. When questions are asked, these questions rarely move beyond lower-order or `fact seeking` enquiries. While this research provides information concerning the frequency and in some cases, the type of questions coaches asks, it fails to report the more discursive nature of coaches` questioning approaches. In order to address such limitations, the purpose of this study was to investigate coach questioning practices (CQPs). We recorded the practices of five academy youth level football coaches` and subjected the data to conversational analysis (CA), This enabled the analysis of interaction between coach and player(s). Findings revealed that CQPs, regardless of coach or context followed similar discursive patterns. In particular, three themes presented themselves in each CQP: (1) coaches` requirements for an immediate player response, (2) leading questions for a desired response, (3) monologist nature of coach/player interaction. This showed that the coach positioned themselves as the gatekeeper of knowledge and learners as passive recipients. This reinforces the messages from previous work that has suggested coaches` ideologies inform their practice, and are stable structures that are difficult to change. We concur with other researchers that there is a need for further investigation in this area to better understand how dominant discourse can be challenged.